La peur de l'autre en soi: du sexisme à l'homophobie - Dorais, Michel; Dutey, Pierre; Welzer-Lang, Daniel (VLB, 1994)
Qu’est-ce que l’homophobie ? C’est l’appréhension de cette femme qui sommeille en chaque homme, de cet homme qui dort en chaque femme, de cet homosexuel ou cette homosexuelle qui, sait-on jamais, n’attend peut-être qu’à s’éveiller en nous.
Section: 302 pages : illustrations ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis